Pertanggungjawaban Penggunaan Dana Hibah Oleh Badan Hukum Keagamaan - Ali Yusran Gea (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
In accordance with Chapter "and Article 1666 of the Civil Code. This grant is directly from the current state budget, namely the state budget (APBN), provincial budget (APBD), and District/City Budget (APBD). The gift giving process is canceled if the given things are not known at the moment or will only be accessible at a later date. Funds for regional activity programs can be financed with grant money sourced from the state budget / APBD. Naturally, there are different ways in which this grant money can be presented, including tangible or immaterial forms offered free of charge by one of the participants. A statement of responsibility proving that the use of funds provided by NPHD has been documented in the format of a grant report (text of a Regional grant agreement). Since the local government is the giver and recipient of the grant, it is officially and materially responsible for both processes. The purpose of the Accountability Report on the use of grants is to demonstrate that the grant funds were used and managed appropriately to achieve the desired results, in accordance with the original purpose of the grant.